Current management approach for left renal vein entrapment syndrome: the so-called 'Nutcracker'' syndrome. (October 2011) - McPhee, James T; Menard, Matthew T
Nutcracker syndrome, or more accurately, left renal vein (LRV) entrapment syndrome, refers to an abnormally narrow angle between the superior mesenteric artery and abdominal aorta leading to symptomatic compression and distal dilatation of the LRV as it traverses between these two structures. This compression of the renal vein in its normal anatomic position has been termed 'anterior nutcracker syndrome''. An analogous syndrome may also occur in patients with a retroaortic LRV, whereby the vein is symptomatically compressed between the aorta and the vertebral bodies. This has been referred to as 'posterior nutcracker syndrome''. In either configuration, the external compression may lead to venous hypertension in a subset of patients that typically manifests as left flank pain and hematuria. It may also be associated with varicocele in men and pelvic congestion syndrome in women. While traditional treatment in symptomatic patients has relied on open surgical repair, the recently demonstrated technical feasibility and favorable short-term follow-up of endovascular stenting has led to its emergence as an enticing treatment option over the last decade. Renal vein compression as an anatomic finding observed on axial imaging is much more common than the associated clinical entity. This variable penetrance of symptom manifestation has led to some controversy over the years with regards to which patients warrant treatment; more recently, the focus of debate has shifted more towards how patients are optimally treated.